Peran Orang Tua dalam Menjaga Kesehatan Mental Anak Usia Dini di Tengah Perkembangan Teknologi - Yenda Puspita; Fitriana (JURNAL ARMADA PENDIDIKAN, 2025)
The advancement of digital technology has had a significant impact on various aspects of life, including the mental health of early childhood. This study aims to analyze the role of parents in maintaining the mental health of children aged 4–6 years amidst the development of digital technology. Using a qualitative approach with a case study method, this study involved 10 parents from AR-Rehan Kindergarten, Pekanbaru, as subjects, with data collection techniques through observation and interviews analyzed using the Miles and Huberman interactive model. The results of the study indicate that the use of technology without supervision can cause mental problems in children, such as anxiety, sleep disorders, and decreased social interaction. The strategies used by parents include active assistance when children use digital devices, setting screen time, selecting age-appropriate content, and strengthening children's social and physical activities. Although there are challenges in managing the use of technology, active parental involvement has been shown to reduce the risk of mental disorders in children. This study confirms that synergy between parents, schools, and the community is needed to create an ecosystem that supports optimal child growth and development in the digital era.